Diffuse Spontaneous Laryngeal Hemorrhage with Trastuzumab - Klute, Lauren; Solverson, Matthew; Bingcang, Christopher M.; Dowdall, Jayme R. (Case Reports in Otolaryngology, 2020)
Drug-induced epithelial hemorrhage of the endolarynx is an unusual etiology of hemoptysis. We present a case of hemoptysis in a young female patient undergoing treatment for metastatic breast cancer with trastuzumab emtansine. Though previously associated with diffuse spontaneous hemorrhage of the gingiva, there have not been reports of laryngeal hemorrhage with trastuzumab emtansine treatment. In this case report, we suggest that trastuzumab emtansine played a contributory role in the development of diffuse epithelial laryngeal hemorrhage and describe the pathophysiology, history, laryngoscopic findings, and management of this condition.